2023
DOI: 10.3389/fimmu.2022.1052424
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the longitudinal humoral response in non-hospitalized SARS-CoV-2-positive individuals at decentralized sites: Outcomes and concordance

Abstract: IntroductionEarly in the COVID-19 pandemic, reagent availability was not uniform, and infrastructure had to be urgently adapted to undertake COVID-19 surveillance.MethodsBefore the validation of centralized testing, two enzyme-linked immunosorbent assays (ELISA) were established independently at two decentralized sites using different reagents and instrumentation. We compared the results of these assays to assess the longitudinal humoral response of SARS-CoV-2-positive (i.e., PCR-confirmed), non-hospitalized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 63 publications
8
18
0
Order By: Relevance
“…For statistical analysis, calibration curves were obtained by serial dilution of the standard [37,38]. As the standard solution was of unknown concentration, the most diluted sample was arbitrarily set at a concentration of 1, hence the term “relative concentration”.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For statistical analysis, calibration curves were obtained by serial dilution of the standard [37,38]. As the standard solution was of unknown concentration, the most diluted sample was arbitrarily set at a concentration of 1, hence the term “relative concentration”.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, integra;on of a recent mathema;cal model [38] allowed transforma;on of the dataset for normaliza;on, enabling calcula;on of sta;s;cal differences in an;gen levels between vaccinated and unvaccinated individuals and between individuals having different job categories or poten;al risk factors. This work is part of a collec;ve effort and stresses the importance of rapidly developing adaptable, decentralized tests for popula;on-level immune surveillance in response to a pandemic, even before centralized tes;ng is available [37,39]. To our knowledge, no other study has reported such an extensive 18-month longitudinal inves;ga;on during the key periods preceding and following the emergence of Omicron in a cohort of highly vaccinated food and retail workers, using both centralized and customized methods to analyze two types of immunoglobulin, three types of epitope, and an;gens to three VOC [40,41], [42].…”
Section: Introduconmentioning
confidence: 99%
“…6 and S6 †). As an important fraction of the cohort was vaccinated either three (>60%) or four times (>20%), or had reported an infection (117 of the 304 participants were declared positive to COVID from an antigen or PCR test, including 99 from December 2021 onward), or showed evidence of natural immunity (>50% of the cohort had eventually been declared positive for natural immunity by ELISA during the longitudinal study 55 ), this surge in antigenic response was sustained until the end of the surveyed period. The data clearly demonstrate the ability of SPR sensing to capture changes in the immune response from individuals in the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…S2 †), where nonlinearities were observed for the in-house colorimetric ELISA (r = 0.37) and chemiluminescence ELISA (r = 0.35). While both ELISA platforms were found to correlate well with each other, 55 lower correlation with the SPR assay is expected, because ELISA measures antibody titers irrespective of their ability to neutralize binding of the spike protein to the ACE-2 receptor. The results indicate that antibody level is a contributing factor in the response of the SPR assay, but not necessarily a major driver.…”
Section: Cross-validation With Established Techniquesmentioning
confidence: 98%
See 1 more Smart Citation